Pengembangan Lembar Kerja Siswa Akuntansi Berbasis Problem Based Learning Pada Siswa Kelas X SMK Taruna Pulokulon Grobogan - Andarwarti, Iin, Prof. Dr. Sutama, M.Pd, Dr. Suyatmini, M.Si (2016)
The aim of the research. Development of student worksheet accounting based problem based learning. The final result of the research is to tasted the effectiveness of student worksheet accounting based problem based learning. Research method. Research and development that includes introduction, field study of theaching management in the school, planning and preparing problem based learning model, implementation of theaching firs cycle, second cycle, and third cycle, and exam of attitude, skill, and learning outcome. The result of the study. LKS based accounting problem based learning at the eleven grade student of SMK Taruna Pulokulon Grobogan can maximize the time of theachang ing the classroom by maximizing the direct instruction and interaction among groups through discussion held during the learning process. Teaching materials ae divided into two types, namely modules and exercises produced by students. Lks based accounting problem based learning method Problem Based Leaning (PBL) in the first, second cycle, and the third cycle, method for increasing creativity, responsibility, and skill of study. The result of creativity was increased with 1.05 in the ten grade student in AK 1 class and 1.41 in AK 2 class. For the responsibility, in the ten grade student in AK 1 class was 0.84 and 1.5 for AK 2 class in the skill aspect also increased with 0.84 X AK1 class, and 1.5 in X AK 2 class. The effectiveness of the model was used covariance analysis test (Ankova) it shows that the level of significant was smaller from 0,05 to 0,00.the researcher concluded that the implementation of LKS-based accounting problem based learning at the ten grade students of SMK Taruna Pulokulon Grobogan effective.